2014
DOI: 10.1074/jbc.m113.536375
|View full text |Cite
|
Sign up to set email alerts
|

Ras Protein Activation Is a Key Event in Activity-dependent Survival of Cerebellar Granule Neurons

Abstract: Background:Contradictory results exist on the survival role of PI3K/Akt and ERK pathways in cerebellar granule neurons. Results: Both pathways are involved in activity-dependent survival of cerebellar granule cells when they are activated by Ras. Conclusion: Ras is a central mediator of survival in cerebellar granule neurons. Significance: The biological significance of PI3K/Akt and ERK pathway activation depends on which monomeric-G-protein is acting upstream.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…Slice Pharmacology-As described previously (43,44), neostriatum from 10-to 12-week-old wild-type male C57BL/6 mice was acutely microdissected from 350-m coronal slices and equilibrated for 30 min with adenosine deaminase (10 g/ml) in Krebs-HCO 3 Ϫ buffer (124 mM NaCl, 4 mM KCl, 26 mM NaHCO 3 , 1.5 mM CaCl 2 , 1.25 mM KH 2 PO 4 , 1.5 mM MgSO 4 , and 10 mM D-glucose (pH 7.4)) oxygenated with 95% O 2 /5% CO 2 followed by another 30 min incubation in fresh Krebs-HCO 3 Ϫ buffer. Some striatal slices were pre-incubated for 1 h in Krebs buffer plus dimethyl sulfoxide vehicle, 40 M U0126, 50 M CP681301, and/or 200 nM or 1 M okadaic acid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Slice Pharmacology-As described previously (43,44), neostriatum from 10-to 12-week-old wild-type male C57BL/6 mice was acutely microdissected from 350-m coronal slices and equilibrated for 30 min with adenosine deaminase (10 g/ml) in Krebs-HCO 3 Ϫ buffer (124 mM NaCl, 4 mM KCl, 26 mM NaHCO 3 , 1.5 mM CaCl 2 , 1.25 mM KH 2 PO 4 , 1.5 mM MgSO 4 , and 10 mM D-glucose (pH 7.4)) oxygenated with 95% O 2 /5% CO 2 followed by another 30 min incubation in fresh Krebs-HCO 3 Ϫ buffer. Some striatal slices were pre-incubated for 1 h in Krebs buffer plus dimethyl sulfoxide vehicle, 40 M U0126, 50 M CP681301, and/or 200 nM or 1 M okadaic acid.…”
Section: Methodsmentioning
confidence: 99%
“…MS analysis was performed on a QSTAR Pulsar I quadrupole time of flight tandem mass spectrometer (Applied Biosystems/ MDS SCIEX) equipped with a nanoelectrospray ion source (MDS Proteomics, Odense, Denmark). For precursor ion scanning, the instrument was set in negative ion mode to detect the PO 3 Ϫ fragment ion at m/z Ϫ79. After data acquisition, the instrument was switched to positive ion mode, and the phosphopeptide sequence and site of phosphorylation were determined by nanoelectrospray-QSTAR Pulsar I quadrupole time of flight MS/MS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of TRPC leads to trans-sarcolemmal Ca 2+ influx to directly increase the intracellular Ca 2+ concentration; it can also lead to trans-sarcolemmal Na + influx to indirectly increase the intracellular Ca 2+ concentration [7]. There is evidence that, in cerebellar granule cells cultured in vitro , when TRPC3 and TRPC6 channels are opened, activation of the Ca 2+ /Ras/MEK/ERK and Ca 2+ /CaM/CaMK signaling pathways can phosphorylate cAMP-response element binding protein (CREB) and increase its transcriptional activity, thereby promoting the survival of neurons [8]. …”
Section: Introductionmentioning
confidence: 99%
“…18,28 We recently reported that the survival role of PI3K/Akt and ERK pathways in CGNs depends on the small G proteins acting upstream. 30 We demonstrated that both pathways are involved in NMDA-mediated neuroprotection when they are activated by Ras. In contrast, the stimulation of the ERK pathway by other members of the small G proteins family, such as Rap1, is not sufficient to promote protection.…”
Section: Molecular Pathways Related To the Neuroprotection Of Cgnsmentioning
confidence: 99%